Impact of biopesticide formulation on tomato (Lycopersicon esculentum): economics and environmental effects - ARORA, SUMITRA; KANOJIA, ASHOK K; KUMAR, ASHOK; SARDANA, H R; SARKAR, SUSHEEL KUMAR (The Indian Journal of Agricultural Sciences, 2013)
The indigenously prepared biopesticide formulation (BPF) @ 10% proved to be the best for tomato crop with lowest EIQ-field use ratings resulting in least or negligible impact on environment. The lowest economics involved proves its high social acceptance. Therefore there is a need to opt traditional knowledge as essential and alternate component of pest management, not only for tomato crop, but also to all major crops, to reduce the load and impact of synthetic chemical pesticides for safer environment. If any pesticide schedule or plant protection activity is able to reduce economics involved in the programme along with minimum total EIQ-FUR level, it would definitely add value to the standard of living of farmers by making that technology, socially acceptable.